Lyapunov‐based EMPC of constrained nonlinear systems with changing economic costs. Issue 4 (20th March 2020) - He, Defeng; Xu, Shan
Abstract: There exist frequent economic cost changes in many process systems due to variations in price, market demand, disturbance, etc. This change switches the economic setpoint of processes throughout their operation and may cause a loss of feasibility and/or stability in economic model predictive control (EMPC). In this paper, we present a novel Lyapunov‐based EMPC scheme for optimization of changing economic costs of constrained nonlinear systems. The dual‐mode paradigm is used to guarantee stability and constraint satisfaction in the presence of changing economic costs. Parameterization control actions are also adopted to decrease the computational effort of solving EMPC optimization. An equilibrium manifold is introduced to unify the terminal regions of local control Lyapunov functions (CLFs) and this enlarges the domain of attraction of the closed‐loop system with EMPC. Moreover, the proposed controller is shown to be always feasible for any change in economic costs and asymptotic stable by providing some CLFs of the nonlinear system. Finally, an example of CSTR is exploited to demonstrate the effectiveness of the proposed scheme, compared with traditional EMPC.